2001
DOI: 10.1081/cnv-100106143
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Shared Decision Making for Prostate Cancer Patients with Low Socioeconomic Status

Abstract: Quality of life (QOL) considerations are important in the treatment decision making process for prostate cancer patients. Although patient involvement in the treatment decision process has been encouraged, low health literacy can limit patient understanding of the complex information about treatments and their probable QOL outcomes and is a barrier to patient participation in the decision-making process. The objectives of the study were to evaluate (i) knowledge, level of satisfaction, and treatment preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(181 citation statements)
references
References 21 publications
6
174
0
1
Order By: Relevance
“…One interpretation is that men with less education, even in an equal access to health care system, may experience greater difficulty understanding educational material on the disease, its treatments, and posttreatment care. 5 Poor understanding of the self-care instructions provided in the urology clinical setting or poor understanding of information on the kinds of posttreatment support available to manage symptoms may contribute to difficulties with the management of symptoms, worry about disease burden and recurrence, and difficulty in adjusting one's lifestyle to treatment schedules and symptoms. Interventional studies provide evidence consistent with this, suggesting that men with low education levels have a deficit of information that can be improved upon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One interpretation is that men with less education, even in an equal access to health care system, may experience greater difficulty understanding educational material on the disease, its treatments, and posttreatment care. 5 Poor understanding of the self-care instructions provided in the urology clinical setting or poor understanding of information on the kinds of posttreatment support available to manage symptoms may contribute to difficulties with the management of symptoms, worry about disease burden and recurrence, and difficulty in adjusting one's lifestyle to treatment schedules and symptoms. Interventional studies provide evidence consistent with this, suggesting that men with low education levels have a deficit of information that can be improved upon.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it is not clear that education level is related to prostate cancer outcomes, such as health-related quality of life (HRQOL), apart from its impact on the treatment choice, previous work has found that men with less education have less knowledge of prostate cancer before diagnosis 3,4 and have poor understanding of prostate cancer and its treatments after diagnosis even after participation in an educational program on prostate cancer. 5 Because poor understanding of prostate cancer and its treatment potentially could contribute to poor management of symptoms and greater disruption to lifestyle, it is important to understand the influence of education on HRQOL and on the specific symptoms associated with prostate cancer and its treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the DAs were developed de novo; 2 trials used a DA developed by Holmes-Rovner et al 35,36 Kim et al used a DA produced by a pharmaceutical company. 37 Most DAs presented information in multiple formats, including written materials (8 trials) 30,31,[33][34][35][36][38][39][40] and multimedia presentations (8 trials), [35][36][37][38][40][41][42][43] and provided individualized information for patients based on their disease stage. Two trials tested interventions involving information exchange via in-person consultation with urologists and a multidisciplinary team.…”
Section: Types Of Das and Control Interventionsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43] The DAs were delivered in 4 settings: hospitals (4 studies), physician's offices (1 study), patient education centers (4 studies), and nonmedical settings such as home or research office (4 studies). Participants were recruited from academic and community settings.…”
Section: Study Settings Recruitment and Participantsmentioning
confidence: 99%
“…Previous studies focused only on QOL by socioeconomic status and the relationship between cancer and marital status (Goodwin et al, 1987;Burström et al, 2001;Kravdal, 2001), and some of these studies did not measure QOL using EQ-VAS or EQ-5D (Kim et al, 1999;Kobayashi et al, 2008). However, this study was cross-sectional in nature; hence, there are limitations in interpreting the causal relationship between QOL and marital status in patients with cancer and survivors of cancer.…”
Section: Discussionmentioning
confidence: 76%